Analisis Rasio Keuangan dan Prediksi Kebangkrutan dengan Model Altman Z-Score pada Perusahaan Semen Tahun 2016-2019 - Daniar Maretta Rastika (Jurnal Acitya Ardana, 2022)
The background of the research in this paper is the bankruptcy of Holcim Indonesia due to the marketing strategy of predatory pricing that conducted by cement companies from China. This study aims to explain financial performance based on financial ratio analysis and bankruptcy prediction to cement companies that have been registered with IDX. The data collection methods used in this study are documentation methods and literature study methods from various books, scientific journals, and other sources, including financial statements and annual reports from six cement companies that have been registered with IDX from2016 to 2019. All data obtained is processed using various financial ratio formulas and bankruptcy predictions of Altman Z-Score model. Research on financial ratio analysis and bankruptcy prediction of the Altman Z-Score model against six objects resulted in INTP as the best performing company due to its excellence in all financial ratios and bankruptcy predictions. While the company with the worst performance is SMCB because almost of all the research conducted, SMCB always at the bottom position or in the distress zone.